The impact of traffic-flow patterns on air quality in urban street canyons. (January 2016) - Thaker, Prashant; Gokhale, Sharad
Abstract: We investigated the effect of different urban traffic-flow patterns on pollutant dispersion in different winds in a real asymmetric street canyon. Free-flow traffic causes more turbulence in the canyon facilitating more dispersion and a reduction in pedestrian level concentration. The comparison of with and without a vehicle-induced-turbulence revealed that when winds were perpendicular, the free-flow traffic reduced the concentration by 73% on the windward side with a minor increase of 17% on the leeward side, whereas for parallel winds, it reduced the concentration by 51% and 29%. The congested-flow traffic increased the concentrations on the leeward side by 47% when winds were perpendicular posing a higher risk to health, whereas reduced it by 17–42% for parallel winds. The urban air quality and public health can, therefore, be improved by improving the traffic-flow patterns in street canyons as vehicle-induced turbulence has been shown to contribute significantly to dispersion. Highlights: CFD is used to study impact of traffic-flow patterns on urban air quality. Facilitating free-flow patterns induce more turbulence in street canyons. Traffic-generated turbulence alters pollutant levels in urban street canyons. Abstract : This study investigates the effect of vehicle-induced-turbulence generated during free-flow traffic pattern in reduction of air pollutant concentrations in urban street canyons.